Numerical analysis of the optimized performance of the electron cyclotron wave system in a HL-2M tokamak - 李景春 龚学余 董家齐 王俊 尹岚 (Chinese physics B, 2016)
The capabilities of current drive, neoclassical tearing mode （NTM） stabilization, and sawtooth control are analyzed for the electron-cyclotron wave （ECW） system in a HL-2M tokamak. Better performance of the upper launcher is demonstrated in comparison with that of a dropped upper launcher, in terms of JEc/Jbs for NTM stabilization and 1ECCD/（Aptor）2 for sawtooth control. 1-MW ECW power is enough for the 3/2 NTM stabilization, and 1.8-MW ECW power is required to suppress 2/1 NTM in a single null divertor equilibrium with 1.2-MA toroidal current with the upper launcher. Optimization simulation of electron-cyclotron current drive （ECCD） is carried out for three mirrors in an equatorial port, indicating that the middle mirror has a good performance compared with the top and bottom mirrors. The results for balanced co- and counter-ECCD in an equatorial port are also presented.